Students' Interest in Online-Based Thematic Learning During The Covid-19 Pandemic - Indryani Amalia; Asis Saefuddin; Dede Rohaniawati (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2021)
This research was motivated by the existence of a circular letter from the Minister of Education and Culture regarding the implementation of education policies during the spread of COVID-19, making face-to-face learning in schools stopped and switching to online learning. The purpose of this study was to determine the online learning practices applied by the teacher in thematic learning of MI AU students in Bogor Regency, as well as to determine students' interest in online thematic learning. The object of this research was 65 people, both men and women. The method used in this research is descriptive quantitative method. The data collection technique was carried out using a questionnaire in which the researcher arranged questions related to students' interest in online thematic learning. Furthermore, the questionnaire data were analyzed using descriptive statistics. The results of research on students' interest in online-based thematic learning during the COVID-19 pandemic at MI AU showed student interest with a percentage of 76.22% of the 22 statement items given to students through a questionnaire. The learning practice uses the WhatsApp group application because the application is easy to use by parents. Thus, students' interest in online-based thematic learning shows a very high interest.